Examining The Politeness Principles in The Oral Tradition of Jawab Dilaman Malay Society in Kemingking Village, Jambi Province - Irma Suryani; Julisah Izar; Rengki Afria (Institut Seni Indonesia Denpasar, 2023)
Pragmatics is a branch of linguistics that examines the external meaning of an utterance that is interpreted by the listener. This study aimed to examine the Politeness Principles in the oral tradition of